“PFH/AGM-CBA/HSV-TK/LIPOSOME-Affibody”: Novel Targeted Nano Ultrasound Contrast Agents for Ultrasound Imaging and Inhibited the Growth of ErbB2-Overexpressing Gastric Cancer Cells - Zhou H; Liu H; Zhang Y; Xin Y; Huang C; Li M; Zhao X; Ding P; Liu Z (Dove Medical Press, 2022)
Houren Zhou,1 Hui Liu,2 Yue Zhang,3 Ying Xin,3 Chi Huang,3 Mingzhong Li,4 Xiaoyun Zhao,2 Pingtian Ding,2 Zhijun Liu3 1Ultrasound Department, The Second Affiliated Hospital of Dalian Medical University, Dalian, People's Republic of China; 2School of Pharmacy, Shenyang Pharmaceutical University, Shenyang, People's Republic of China; 3Ultrasound Department, Shengjing Hospital, China Medical University, Shenyang, People's Republic of China; 4School of Pharmacy, De Montfort University, Leicester, LE1 9BH, UKCorrespondence: Zhijun Liu, Ultrasound Department, Shengjing Hospital, China Medical University, 36 Sanhao Street, Shenyang, Liaoning Province, 110004, People's Republic of China, Email liuzj1@sj-hospital.orgObjective: Gastric cancer is one of the most lethal malignancies in the world. However, the current research on the diagnosis and treatment of nano-ultrasound contrast agents in the field of tumor is mostly focused on breast cancer, ovarian cancer, prostate cancer, liver cancer, etc. Due to the interference of gas in the stomach, there is no report on the treatment of gastric cancer. Herpes simplex virus thymidine kinase/ganciclovir (HSV-TK/GCV) therapy system is the most mature tumor suicide gene in cancer treatment. At the same time, in order to improve its safety and efficiency, we designed a gastric tumor targeted ultrasound-triggered phase-transition nano ultrasound contrast agent PFH/AGM-CBA/HSV-TK/Liposome (PAHL)-Affibody complex.Methods: In our study, guanidinylated SS-PAAs polymer poly(agmatine/N, N'-cystamine-bis-acrylamide) (AGM-CBA) was used as a nuclear localization vector of suicide gene to form a polyplex, perfluorohexane (PFH) was used as ultrasound contrast agent, liposomes were used to encapsulate perfluorohexane droplets and the polyplexes of AGM-CBA/HSV-TK, and affibody molecules were conjugated to the prepared PAHL in order to obtain a specific targeting affinity to human epidermal growth factor receptor type 2 (ErbB2) at gastric cancer cells. With the aid of ultrasound targeted microbubble destruction technology and the nuclear localization effect of AGM-CBA vector, the transfection efficiency of the suicide gene in gastric cancer cells was significantly increased, leading to significant apoptosis of gastric cancer cells.Results: It was shown that PAHL-Affibody complex was nearly spherical with an average diameter of 560 ± 28.9 nm, having higher and specific affinity to ErbB2 (+) gastric cells. In vitro experiments further confirmed that PAHL could target gastric cancer cells expressing ErbB2. In a contrast-enhanced ultrasound scanning study, the prepared ultrasound-triggered phase-change nano-ultrasound contrast agent, PAHL, showed improved ultrasound enhancement effects. With the application of the low-frequency ultrasound, the gene transfection efficiency of PAHL was significantly improved,  thereby inducing significant apoptosis in gastric cancer cells.Conclusion: This study constructs PFH/AGM-CBA/HSV-TK/Liposome-Affibody nano ultrasound contrast agent, which provides new ideas for the treatment strategy of ErbB2-positive gastric cancer and provides some preliminary experimental basis for its inhibitory effect.Keywords: Herpes simplex virus thymidine kinase/ganciclovir, poly (agmatine/N, N'-cystamine-bis-acrylamide), ErbB2 targeting, gene transfection, low-frequency ultrasound